Age and tumor size predicts lymph node involvement in Hürthle Cell Carcinoma - Guerrero, Marlon A. (Ivyspring International Publisher, 2010)
Introduction: Hürthle cell carcinoma (HCC) is a rare tumor that tends to metastasize to the lymph nodes. Some studies have correlated size of Hürthle cell tumors with the risk of malignancy. Whether the size of HCC correlates with the risk of lymph node (LN) metastases, to our knowledge has not been addressed. Methods: A retrospective analysis was performed on all patients diagnosed with HCC on final pathology between 1997 and 2008. The tumor size and lymph node status was obtained for each patient. The data were analyzed utilizing Student's t-test and the Fisher's exact test to calculate the two-tailed p-value. Results: Out of 39 patients diagnosed with HCC 3(8%) had LN metastases; 1 had ipsilateral central LN metastasis and 2 had ipsilateral central and lateral LN metastasis. LN dissection was performed in patients with known metastasis (2 were evident on preoperative ultrasound and 1 intraoperatively). Patients with LN metastasis were older than those without (mean age: 86.7 and 56.4 years, respectively), had larger tumors (mean size: 6 and 4 cm) and were commonly male (2 of 3). No tumor < 5cm presented with lymph node involvement (3/15 with >5cm cancer had node metastasis, 0/24 with <5cm cancer had node metastasis). Conclusions: Similar to what has been found in patients with papillary thyroid cancer, older male patients with Hürthle cell carcinomas greater than 5cm are more likely to have lymph node metastasis. Our data suggest that these patients may benefit from a prophylactic ipsilateral central neck dissection at the time of their initial operation.